Regionally Metastatic Merkel Cell Carcinoma Associated with Paraneoplastic Anti-N-methyl-D-aspartate Receptor Encephalitis - Sophia Z. Shalhout; Kevin S. Emerick; Peter M. Sadow; Jenny J. Linnoila; David M. Miller (Case Reports in Oncological Medicine, 2020)
Merkel cell carcinoma (MCC) is a rare and aggressive cutaneous neuroendocrine cancer with a high risk of recurrence and metastasis. MCC is generally associated with advanced age, fair skin, sun exposure, immunosuppression, and in the majority of cases, the Merkel cell polyomavirus. Neuroendocrine malignancies are associated with a variety of paraneoplastic neurological syndromes (PNS), characterized as autoimmune responses to malignancy-associated expression of neural antigens. Our literature review underscores previous case reports of MCC-associated PNS with voltage-gated calcium channel (VGCC) and anti-Hu (or ANNA-1) autoantibodies. We present the case of a 59-year-old male with regionally metastatic Merkel cell carcinoma complicated by the paraneoplastic manifestation of anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis. His primary lower neck subcutaneous MCC and metastasis were initially treated with surgery. Additional recurrent lymph node metastases were successfully treated with definitive intensity-modulated radiation therapy. His PNS improved with rituximab therapy. Although rare, this case highlights that in the setting of seizures and prominent psychiatric symptoms accompanying an MCC diagnosis, evaluation for autoimmune paraneoplastic encephalitis is warranted. Awareness and detection of preexisting PNS are crucial in the era of immune checkpoint inhibitors (ICI) for advanced MCC, where treatment with ICI has the potential to exacerbate preexisting autoimmune PNS and lead to worsened or even lethal neurologic immune-related adverse events (nirAEs).